(untitled) (Global Journal of Human-Social Science, 2012)
The advent of HIV/AIDS has brought severe health challenges to the population and has added to the problem of health care. More case loads are entering the hospitals as new cases of infected persons are reported. It is necessary to look at the salient risk factors which are often neglected and disregarded. The study was carried out in two urban and rural settings of Cross River and Akwa Ibom States of Nigeria. The population of the study was 500 respondents randomly sampled. The results indicated that, Global System of Mobil Telecommunication (GSM) facilitate networking of people within the population. The respondents agreed that this networking often resulted in illicit sexual behaviour which serves as a primary source of contracting HIV/AIDS. The strong opinion of the research is that, there is need to carryout education among the populace on a more positive use of GSM facility. The education are to be directed on youths within the population for behaviour modification on the use of GSM facility.